Horizontally Acquired Cellulases Assist the Expansion of Dietary Range in Pristionchus Nematodes. (3rd January 2022) - Han, Ziduan; Sieriebriennikov, Bogdan; Susoy, Vladislav; Lo, Wen-Sui; Igreja, Catia; Dong, Chuanfu; Berasategui, Aileen; Witte, Hanh; Sommer, Ralf J
Abstract: Horizontal gene transfer (HGT) enables the acquisition of novel traits via non-Mendelian inheritance of genetic material. HGT plays a prominent role in the evolution of prokaryotes, whereas in animals, HGT is rare and its functional significance is often uncertain. Here, we investigate horizontally acquired cellulase genes in the free-living nematode model organism Pristionchus pacificus . We show that these cellulase genes 1) are likely of eukaryotic origin, 2) are expressed, 3) have protein products that are secreted and functional, and 4) result in endo-cellulase activity. Using CRISPR/Cas9, we generated an octuple cellulase mutant, which lacks all eight cellulase genes and cellulase activity altogether. Nonetheless, this cellulase-null mutant is viable and therefore allows a detailed analysis of a gene family that was horizontally acquired. We show that the octuple cellulase mutant has associated fitness costs with reduced fecundity and slower developmental speed. Furthermore, by using various Escherichia coli K-12 strains as a model for cellulosic biofilms, we demonstrate that cellulases facilitate the procurement of nutrients from bacterial biofilms. Together, our analysis of cellulases in Pristionchus provides comprehensive evidence from biochemistry, genetics, and phylogeny, which supports the integration of horizontally acquired genes into the complex life history strategy of this soil nematode.